Hydrolysis method for preparing electronic-grade metatitanic acid by sulfuric acid process

The preparation of electronic grade metatitanic acid through the sulfuric acid process solves the problem that titanium dioxide does not meet the electronic grade requirements in the traditional process, and achieves the preparation of metatitanic acid with high specific surface area, purity and particle size, providing high-quality raw materials for electronic materials and improving Application performance.

CN119143172APending Publication Date: 2024-12-17PANZHIHUA UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411333249.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The titanium dioxide prepared by the traditional sulfuric acid titanium dioxide process does not meet the high specific surface area, purity and particle size requirements of electronic grade TiO2, and it is difficult to meet the application performance requirements of electronic materials.

Method used

The electronic grade metatitanium acid is prepared by sulfuric acid. The industrial titanium liquid is preheated and alkali liquid is added to form a seed solution. The hydrolysis temperature and time are controlled, the microboiling state is maintained, and the water is diluted. Finally, it is filtered and washed. Electronic grade metatitanic acid with large specific surface area, high purity and suitable particle size is obtained.

Benefits of technology

The preparation of electronic grade metatitanic acid with a specific surface area greater than 350m2/g and a TiO2 purity of 99% or more is achieved, providing high-quality raw materials for electronic ceramic materials and lithium iron phosphate battery materials, and improving the application performance of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005057590980000061
    Figure BDA0005057590980000061
Patent Text Reader

Abstract

The invention relates to a hydrolysis method for preparing electronic-grade metatitanic acid by a sulfuric acid process, and belongs to the technical field of fine chemical engineering. The method comprises the following steps that firstly, industrial titanium liquid is preheated to 96 + / -2 DEG C, and preheated industrial titanium liquid is obtained; adding alkali liquor into the industrial titaniferous solution serving as a raw material to obtain a seed crystal solution; then, the seed crystal solution is added into the preheated industrial titanium solution, the temperature is kept at 96 + / -1 DEG C for 20 + / -1 min, and a mixed titanium solution is obtained; heating the mixed titaniferous solution to boil, keeping a slight boiling state, and stopping heating and stirring for curing when the mixed titaniferous solution is hydrolyzed to a gray point, so as to obtain a hydrolyzed titaniferous solution; heating the hydrolyzed titaniferous solution again to boil, maintaining a slight boiling state, boiling again for 2-2.5 hours, adding dilution water, boiling again for 3 + / -0.2 hours, and ending hydrolysis to obtain hydrolyzed slurry; and sequentially filtering and washing the hydrolyzed slurry, and squeezing the hydrolyzed slurry by a diaphragm to obtain the electronic-grade metatitanic acid. The metatitanic acid prepared by the method is large in specific surface area (greater than or equal to 350m < 2 > / g) and high in purity (TiO2 is greater than or equal to 99%).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fine chemical industry, and specifically relates to a hydrolysis method for preparing electronic grade metatitanic acid by sulfuric acid process. Background Art

[0002] Electronic grade high purity titanium dioxide is widely used in battery materials, catalyst carriers, ultraviolet absorbers, special glass, electronic ceramics, thermistors, semiconductor capacitors, strontium titanate varistors and other fields. Adding ultrafine high purity electronic grade titanium dioxide to materials such as lithium iron phosphate batteries can effectively improve the conductivity, tap density, and lithium ion diffusion rate of the material battery, stabilize the battery material structure, and reduce the electrochemical impedance of the lithium iron phosphate battery during the charging and discharging process, thereby improving the cycle stability, safety and life of the lithium iron phosphate battery. Titanium dioxide produced by the traditional sulfuric acid method titanium dioxide process has the advantages of low cost and mature process, but its specific surface area and purity do not meet the application requirements of electronic grade TiO2.

[0003] The composition structure of hydrolyzed titanic acid has an important impact on the application standards of electronic-grade TiO2. Titanic acid with high specific surface area and low impurity content is a prerequisite for ensuring the application requirements of electronic-grade TiO2. Titanic acid with high specific surface area, small particle size distribution and narrow aspect ratio is more conducive to making the mixture more uniform when mixed with other raw materials, which is beneficial to improving the uniformity and consistency of the composition structure of electronic materials, thereby improving the application performance of electronic materials. Therefore, it is urgent to develop the preparation technology of electronic-grade titanic acid with large specific surface area, high purity and suitable particle size. Summary of the invention

[0004] The invention provides a hydrolysis method for preparing electronic grade metatitanic acid by a sulfuric acid process.

[0005] The technical solution of the present invention is as follows:

[0006] The present invention provides a hydrolysis method for preparing electronic grade metatitanic acid by a sulfuric acid process, comprising the following steps:

[0007] (1) preheating industrial titanium liquid to 96±2° C. to obtain preheated industrial titanium liquid;

[0008] (2) adding alkaline solution to the industrial titanium liquid in step (1) as a raw material to obtain a seed solution;

[0009] (3) adding the seed solution to the preheated industrial titanium liquid and maintaining the temperature at 96±1°C for 20±1min to obtain a mixed titanium liquid;

[0010] (4) After step (3), the mixed titanium liquid is heated to boiling within 10 to 15 minutes and maintained at a slightly boiling state. When the mixture is hydrolyzed to the graying point, the heating is stopped and the mixture is stirred and aged for 30±2 minutes, and the aging temperature is maintained at 100°C to 103°C to obtain a hydrolyzed titanium liquid;

[0011] (5) After step (4) is completed, heating and stirring are turned on, and the hydrolyzed titanium liquid is heated to boiling again within 10 minutes to 15 minutes, and a slightly boiling state is maintained. After boiling again for 2 hours to 2.5 hours, dilution water is added, and the total titanium concentration of the hydrolysis system is maintained at 146 g / L to 153 g / L. After boiling again for 3±0.2 hours, the hydrolysis is terminated to obtain a hydrolyzed slurry;

[0012] (6) The hydrolyzed slurry is filtered, washed, and then pressed through a diaphragm to obtain electronic grade titanic acid.

[0013] The industrial titanium liquid described in the invention is obtained by subjecting titanium concentrate to the processes of acid hydrolysis, leaching, reduction and preliminary concentration.

[0014] The slightly boiling state described in the present invention refers to a state in which the liquid is close to boiling but not completely boiling during the heating process. In the present invention, the slightly boiling state refers to the state in which small bubbles are tumbling on the surface of the mixed titanium liquid and the hydrolyzed titanium liquid, rather than continuously bubbling.

[0015] The graying point mentioned in the present invention refers to the critical point of titanium liquid hydrolysis, which is a core point in the hydrolysis process of titanium dioxide production. Seed crystals are added to titanium liquid to gradually induce the titanium liquid to hydrolyze and precipitate metatitanic acid hydrolyzed particles; as the hydrolysis proceeds further, the color of the hydrolysis system gradually changes from black to olive green and then to steel gray, and this moment is the graying point.

[0016] There are two ways to induce hydrolysis of titanium liquid: self-generated seeds and external seeds. On the one hand, self-generated seed hydrolysis requires high concentration of titanium liquid, which leads to large steam consumption and high cost during concentration. On the other hand, self-generated seeds are prone to cause wide particle distribution during the hydrolysis process, which is not conducive to increasing the specific surface area of ​​titanic acid and removing impurities, thus failing to meet the requirements of electronic grade titanic acid.

[0017] The slightly boiling state is one of the key factors in controlling the more uniform nucleation and growth of titanic acid. The obtained titanic acid particle size is more uniform, which is convenient for meeting the relevant index requirements of electronic grade titanic acid. If it is completely boiled, the shear force of the boiling bubbles and the disturbance of the hydrolysis system will increase, which will easily cause uneven hydrolysis and too wide distribution of titanic acid particle size, affecting the specific surface area and purity and other indicators, and thus causing failure to meet the requirements of electronic grade titanic acid.

[0018] In a specific embodiment, the total titanium concentration of the industrial titanium liquid is 155g / L to 170g / L in terms of TiO2 mass, the F value is 1.84 to 1.90, the iron-titanium ratio is 0.60 to 0.80, and the trivalent titanium content is 1g / L to 3g / L.

[0019] In a specific embodiment, the total titanium concentration of the industrial titanium liquid is 160g / L to 170g / L based on the mass of TiO2, the F value is 1.86 to 1.88, the iron-titanium ratio is 0.68 to 0.78, and the trivalent titanium content is 1.5g / L to 2.5g / L.

[0020] In a specific embodiment, in step (2), the mass ratio of the total TiO2 mass in the industrial titanium liquid to the soda ash in the alkali solution is 0.13-0.17; the alkali solution is a sodium hydroxide aqueous solution with a mass concentration of 9%-11%.

[0021] In a specific embodiment, the total titanium concentration of the seed solution is 130 g / L to 137 g / L based on the mass of TiO2, the seed F value is 1.62 to 1.69, and the stability is 125 mL to 150 mL.

[0022] In a specific embodiment, the total titanium concentration of the seed solution is 133 g / L to 135 g / L based on the mass of TiO2, and the seed F value is 1.65 to 1.67.

[0023] In a specific embodiment, in step (3), the mass ratio of the seed solution added is 2.0% to 2.6%; preferably, the mass ratio of the seed solution added is 2.1% to 2.4%.

[0024] In the present invention, the mass ratio of the seed solution added is calculated according to the mass ratio of the TiO2 in the seed solution to the mass of TiO2 in the titanium liquid.

[0025] In one embodiment, in step (6), the iron impurity content is maintained below 30 ppm after washing.

[0026] In one embodiment, the washing in step (6) includes a first wash, a bleaching wash, a rinse, and a third wash.

[0027] In the present invention, the first washing, bleaching, rinsing and third washing are specifically: the first washing is performed with warm water at 50°C to 60°C, followed by bleaching with sulfuric acid solution + trivalent titanium, followed by rinsing with warm water at 50°C to 60°C, and finally, the pH value of the slurry is adjusted to 9 to 10 with ammonia water and then the third washing is performed with warm water at 50°C to 60°C. The main purpose of washing is to control the Fe content to be less than 30ppm.

[0028] In a specific embodiment, the electronic grade metatitanic acid has a specific surface area greater than 350 m 2 / g, TiO2 purity is greater than or equal to 99%.

[0029] The particle size of the electronic grade metatitanic acid prepared by the present invention is measured by a Malvern nanoparticle size analyzer. 50 =0.81μm~0.90μm,D 10 =0.51μm~0.58μm,D 90 =1.39μm~1.51μm.

[0030] In the present invention, the purity of TiO2 is the content of titanium dioxide corresponding to the content of electronic grade metatitanic acid calcined at 1000°C for 2 hours, after all impurities are deducted and measured.

[0031] Beneficial effects of the present invention:

[0032] (1) The present invention is based on the existing sulfuric acid process titanium dioxide technology, and adopts the control of titanium liquid index, seed index, total titanium concentration of the hydrolysis system, washing and impurity removal to obtain a large specific surface area (≥350m 2 / g), high purity (TiO2≥99%) and suitable particle size electronic grade metatitanic acid, providing high-quality raw materials for applications such as electronic grade titanium dioxide.

[0033] (2) The metatitanic acid prepared by the present invention is mainly used in electronic ceramic materials (barium titanate, strontium titanate, etc.), and can also be used in lithium iron phosphate battery materials. When used, it is directly added to the mixed material in the form of metatitanic acid, and then the corresponding material is prepared by a high-temperature solid phase method. DETAILED DESCRIPTION

[0034] The present invention is further described below with specific examples, but the embodiments of the present invention are not limited thereto.

[0035] Example 1

[0036] The invention adopts the process of thermal hydrolysis with added crystal seeds, and preheats the industrial titanium liquid with a total titanium concentration (in terms of TiO2 mass) of 165 g / L, an F value of 1.87, an iron-titanium ratio of 0.74, and a trivalent titanium content of 2.5 g / L to 96±1°C; the industrial titanium liquid with the same concentration is used as a raw material to add an alkali solution (sodium hydroxide aqueous solution) to prepare a crystal seed solution, wherein the total titanium concentration of the prepared crystal seed solution is 135 g / L, the crystal seed F value is 1.67, and the stability is 128 mL, and the prepared crystal seed solution is maintained at 96±1°C, and the crystal seed solution is quickly added to the preheated titanium liquid at a mass ratio of 2.4% of the total titanium, and maintained at 96±1°C for 20 minutes; within 12 minutes, the crystal seed solution is added to the preheated titanium liquid at a mass ratio of 2.4%. The titanium liquid is heated to boiling and maintained in a slightly boiling state. The conventional sulfuric acid method titanium dioxide hydrolysis process is operated. When the hydrolysis reaches the graying point, the heating and stirring are stopped for 30 minutes, and the aging temperature is maintained at 102°C; after the aging is completed, the heating and stirring are turned on, and the hydrolyzed titanium liquid is heated to boiling again in 12 minutes, and maintained in a slightly boiling state; after boiling again for 2.5 hours, dilution water is added, and the total titanium concentration of the hydrolysis system is maintained at 150g / L. The hydrolysis is terminated after boiling again for 3 hours. The hydrolysis slurry is filtered, washed once, bleached, rinsed, and washed three times until the iron impurity content is less than 30ppm, and then pressed by a diaphragm to obtain electronic grade titanic acid. The test results of the electronic grade titanic acid and titanium dioxide content prepared in Example 1 are listed in Table 1.

[0037] Example 2

[0038] The invention adopts the process of thermal hydrolysis with added crystal seeds, and preheats the industrial titanium liquid with a total titanium concentration (in terms of TiO2 mass) of 170 g / L, an F value of 1.88, an iron-titanium ratio of 0.68, and a trivalent titanium content of 2.1 g / L to 96±1°C; the industrial titanium liquid with the same concentration is used as a raw material to add an alkali solution (sodium hydroxide aqueous solution) to prepare a crystal seed solution, wherein the total titanium concentration of the prepared crystal seed solution is 133 g / L, the crystal seed F value is 1.64, and the stability is 132 mL, and the prepared crystal seed solution is maintained at 96±1°C, and the crystal seed solution is quickly added to the preheated titanium liquid at a mass ratio of 2.2% of the total titanium, and maintained at 96±1°C for 20 minutes; within 13 minutes, the crystal seed solution is added to the preheated titanium liquid at a mass ratio of 2.2%. The titanium liquid is heated to boiling and maintained in a slightly boiling state. The conventional sulfuric acid method titanium dioxide hydrolysis process is operated. When the hydrolysis reaches the graying point, the heating and stirring are stopped for 30 minutes, and the aging temperature is maintained at 101°C; after the aging is completed, the heating and stirring are turned on, and the hydrolyzed titanium liquid is heated to boiling again in 14 minutes, and maintained in a slightly boiling state; after boiling again for 2.2 hours, dilution water is added, and the total titanium concentration of the hydrolysis system is maintained at 153g / L. The hydrolysis is terminated after boiling again for 3 hours. The hydrolysis slurry is filtered, washed once, bleached, rinsed, and washed three times until the iron impurity content is less than 30ppm, and then pressed by a diaphragm to obtain electronic grade titanic acid. The test results of the electronic grade titanic acid and titanium dioxide content prepared in Example 2 are listed in Table 1.

[0039] Example 3

[0040] The invention adopts the process of thermal hydrolysis with added crystal seeds, and preheats the industrial titanium liquid with a total titanium concentration (in terms of TiO2 mass) of 155 g / L, an F value of 1.85, an iron-titanium ratio of 0.80, and a trivalent titanium content of 3.0 g / L to 96±1°C; the industrial titanium liquid with the same concentration is used as a raw material to add an alkali solution (sodium hydroxide aqueous solution) to prepare a crystal seed solution, wherein the total titanium concentration of the prepared crystal seed solution is 137 g / L, the crystal seed F value is 1.63, and the stability is 130 mL, and the prepared crystal seed solution is maintained at 96±1°C, and the crystal seed solution is quickly added to the preheated titanium liquid at a mass ratio of 2.6% of the total titanium, and maintained at 96±1°C for 20 minutes; within 11 minutes, the crystal seed solution is added to the preheated titanium liquid at a mass ratio of 2.6%. The titanium liquid is heated to boiling and maintained in a slightly boiling state. The conventional sulfuric acid method titanium dioxide hydrolysis process is operated. When the hydrolysis reaches the graying point, the heating and stirring are stopped for 30 minutes, and the aging temperature is maintained at 100°C; after the aging is completed, the heating and stirring are turned on, and the hydrolyzed titanium liquid is heated to boiling again in 13 minutes, and maintained in a slightly boiling state; 2.0 hours after boiling again, dilution water is added, and the total titanium concentration of the hydrolysis system is maintained at 147g / L, and the hydrolysis is terminated after boiling again for 3 hours. The hydrolysis slurry is filtered, washed once, bleached, rinsed, and washed three times until the iron impurity content is less than 30ppm, and then pressed by a diaphragm to obtain electronic grade titanic acid. The test results of the electronic grade titanic acid and titanium dioxide content prepared in Example 3 are listed in Table 1.

[0041] Example 4

[0042] The invention adopts the process of thermal hydrolysis with added crystal seeds, and preheats the industrial titanium liquid with a total titanium concentration (in terms of TiO2 mass) of 160 g / L, an F value of 1.84, an iron-titanium ratio of 0.60, and a trivalent titanium content of 1.1 g / L to 96±1°C; uses the industrial titanium liquid with the same concentration as the raw material and adds alkali solution (sodium hydroxide aqueous solution) to prepare the seed solution, wherein the total titanium concentration of the prepared seed solution is 130 g / L, the crystal seed F value is 1.62, and the stability is 125 mL, and the prepared seed solution is maintained at 96±1°C, and the seed solution is quickly added to the preheated titanium liquid at a mass ratio of 2.0% of the total titanium, and maintained at 96±1°C for 20 minutes; within 10 minutes, The titanium liquid is heated to boiling and maintained in a slightly boiling state. The conventional sulfuric acid method titanium dioxide hydrolysis process is operated. When the hydrolysis reaches the graying point, the heating and stirring are stopped for 30 minutes, and the aging temperature is maintained at 101°C; after the aging is completed, the heating and stirring are turned on, and the hydrolyzed titanium liquid is heated to boiling again in 11 minutes, and maintained in a slightly boiling state; 2.0 hours after boiling again, dilution water is added, and the total titanium concentration of the hydrolysis system is maintained at 146g / L, and the hydrolysis is terminated after boiling again for 3 hours. The hydrolysis slurry is filtered, washed once, bleached, rinsed, and washed three times until the iron impurity content is less than 30ppm, and then pressed by a diaphragm to obtain electronic grade titanic acid. The test results of the electronic grade titanic acid and titanium dioxide content prepared in Example 4 are listed in Table 1.

[0043] Example 5

[0044] The invention adopts the process of thermal hydrolysis with added crystal seeds, and preheats the industrial titanium liquid with a total titanium concentration (in terms of TiO2 mass) of 163 g / L, an F value of 1.86, an iron-titanium ratio of 0.77, and a trivalent titanium content of 2.4 g / L to 96±1°C; the industrial titanium liquid with the same concentration is used as a raw material to add an alkali solution (sodium hydroxide aqueous solution) to prepare a crystal seed solution, wherein the total titanium concentration of the prepared crystal seed solution is 134 g / L, the crystal seed F value is 1.66, and the stability is 134 mL, and the prepared crystal seed solution is maintained at 96±1°C, and the crystal seed solution is quickly added to the preheated titanium liquid at a mass ratio of 2.3% of the total titanium, and maintained at 96±1°C for 20 minutes; within 15 minutes, the crystal seed solution is added to the preheated titanium liquid at a mass ratio of 2.3%. The titanium liquid is heated to boiling and maintained in a slightly boiling state. The conventional sulfuric acid method titanium dioxide hydrolysis process is operated. When the hydrolysis reaches the graying point, the heating and stirring are stopped for 30 minutes, and the aging temperature is maintained at 103°C; after the aging is completed, the heating and stirring are turned on, and the hydrolyzed titanium liquid is heated to boiling again in 14 minutes, and maintained in a slightly boiling state; after boiling again for 2.4 hours, dilution water is added, and the total titanium concentration of the hydrolysis system is maintained at 151g / L. The hydrolysis is terminated after boiling again for 3 hours. The hydrolysis slurry is filtered, washed once, bleached, rinsed, and washed three times until the iron impurity content is less than 30ppm, and then pressed by a diaphragm to obtain electronic grade titanic acid. The test results of the electronic grade titanic acid and titanium dioxide content prepared in Example 5 are listed in Table 1.

[0045] Comparative Example 1

[0046] The invention adopts the process of thermal hydrolysis with added crystal seeds, and preheats the industrial titanium liquid with a total titanium concentration (in terms of TiO2 mass) of 190 g / L, an F value of 1.82, an iron-titanium ratio of 0.37, and a trivalent titanium content of 2.0 g / L to 96±1°C; the industrial titanium liquid with the same concentration is used as a raw material and an alkali solution (sodium hydroxide aqueous solution) is added to prepare a crystal seed solution, wherein the total titanium concentration of the prepared crystal seed solution is 123 g / L, the crystal seed F value is 1.72, and the stability is 120 mL, and the prepared crystal seed solution is maintained at 96±1°C, and the crystal seed solution is quickly added to the preheated titanium liquid at a mass ratio of 2.5% of the total titanium, and is maintained at 96±1°C for 20 minutes; within 9 minutes, Heat the titanium liquid to boiling and keep it in a slightly boiling state. According to the conventional sulfuric acid method titanium dioxide hydrolysis process, when the hydrolysis reaches the graying point, stop heating and stirring to mature for 30 minutes, and maintain the maturation temperature at 105°C; after the maturation, turn on heating and stirring, and heat the hydrolyzed titanium liquid to boiling again in 11 minutes, and maintain a slightly boiling state; add dilution water 1.7 hours after boiling again, and maintain the total titanium concentration of the hydrolysis system at 160g / L, and stop the hydrolysis after boiling again for 3 hours. The hydrolysis slurry is filtered, washed once, bleached, rinsed, and washed three times until the iron impurity content is less than 30ppm, and then pressed by a diaphragm to obtain titanic acid. The test results of the titanic acid and titanium dioxide content prepared in Comparative Example 1 are listed in Table 1.

[0047] Comparative Example 2

[0048] Using an external seed thermal hydrolysis process, an industrial titanium liquid with a total titanium concentration (in terms of TiO2 mass) of 152 g / L, an F value of 1.92, an iron-titanium ratio of 0.82, and a trivalent titanium content of 1.4 g / L is preheated to 96±1°C; an industrial titanium liquid with the same concentration is used as a raw material and an alkali solution (sodium hydroxide aqueous solution) is added to prepare a seed solution, wherein the total titanium concentration of the prepared seed solution is 140 g / L, the seed F value is 1.61, and the stability is 117 mL. The prepared seed solution is maintained at 96±1°C, and the seed solution is quickly added to the preheated titanium liquid at a mass ratio of 1.8% of the total titanium, and maintained at 96±1°C for 20 minutes; after 8 minutes The titanium liquid is heated to boiling and maintained in a slightly boiling state. The conventional sulfuric acid method titanium dioxide hydrolysis process is operated. When the hydrolysis reaches the graying point, the heating and stirring are stopped for 30 minutes, and the aging temperature is maintained at 98°C; after the aging is completed, the heating and stirring are turned on, and the hydrolyzed titanium liquid is heated to boiling again in 11 minutes, and maintained in a slightly boiling state; 1.8 hours after boiling again, dilution water is added, and the total titanium concentration of the hydrolysis system is maintained at 142g / L, and the hydrolysis is terminated after boiling again for 3 hours. The hydrolysis slurry is filtered, washed once, bleached, rinsed, and washed three times until the iron impurity content is less than 30ppm, and then pressed by a diaphragm to obtain titanic acid. The test results of the titanic acid and titanium dioxide content prepared in Comparative Example 2 are listed in Table 1.

[0049] Comparative Example 3

[0050] The invention adopts the process of thermal hydrolysis with added crystal seeds, and preheats the industrial titanium liquid with a total titanium concentration (in terms of TiO2 mass) of 180 g / L, an F value of 1.81, an iron-titanium ratio of 0.51, and a trivalent titanium content of 1.8 g / L to 96±1°C; uses the industrial titanium liquid with the same concentration as the raw material to add alkali solution (sodium hydroxide aqueous solution) to prepare a crystal seed solution, wherein the total titanium concentration of the prepared crystal seed solution is 120 g / L, the crystal seed F value is 1.75, and the stability is 129 mL, and the prepared crystal seed solution is maintained at 96±1°C, and the crystal seed solution is quickly added to the preheated titanium liquid at a mass ratio of 2.3% of the total titanium, and is maintained at 96±1°C for 20 minutes; and at 9 minutes The titanium liquid is heated to boiling and maintained in a slightly boiling state. The conventional sulfuric acid method titanium dioxide hydrolysis process is operated. When the hydrolysis reaches the graying point, the heating and stirring are stopped for 30 minutes, and the aging temperature is maintained at 104°C; after the aging is completed, the heating and stirring are turned on, and the hydrolyzed titanium liquid is heated to boiling again in 9 minutes, and maintained in a slightly boiling state; 2.0 hours after boiling again, dilution water is added, and the total titanium concentration of the hydrolysis system is maintained at 157g / L. The hydrolysis is terminated after boiling again for 3 hours. The hydrolysis slurry is filtered, washed once, bleached, rinsed, and washed three times until the iron impurity content is less than 30ppm, and then pressed by a diaphragm to obtain titanic acid. The test results of the titanic acid and titanium dioxide content prepared in Comparative Example 3 are listed in Table 1.

[0051] Table 1. Composition, particle size and specific surface area of ​​electronic grade metatitanic acid prepared in different embodiments and comparative examples

[0052]

[0053] * Note: The TiO2 content is the content of titanium dioxide corresponding to the electronic grade metatitanic acid calcined at 1000℃ for 2h, after all impurities are deducted. # The TiO2 solid content is the TiO2 content measured by chemical method in electronic grade metatitanic acid. The particle size is measured by Malvern nanoparticle sizer.

[0054] The ratio of the total content of Fe, K, and Na impurities to the solid content of TiO2 is calculated based on the TiO2 content converted to 100%. The normal range of the embodiment of this ratio is within 0.0018. The Fe content of the electronic grade metatitanic acid prepared by the present invention (converted to Fe2O3 is 0.0022% to 0.0036%); the potassium and sodium (K2O+Na2O) content is 0.0060% to 0.0083%.

[0055] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention still fall within the scope covered by the present invention.

Claims

1. A hydrolysis method for preparing electronic grade metatitanic acid by sulfuric acid process, characterized in that: The steps include: (1) preheating industrial titanium liquid to 96±2° C. to obtain preheated industrial titanium liquid; (2) using the industrial titanium liquid of step (1) as a raw material, adding alkaline solution to obtain a seed solution; (3) adding the seed solution to the preheated industrial titanium liquid and maintaining the temperature at 96±1°C for 20±1min to obtain a mixed titanium liquid; (4) After step (3), the mixed titanium liquid is heated to boiling within 10 to 15 minutes and maintained at a slightly boiling state. When the mixture is hydrolyzed to the graying point, the heating is stopped and the mixture is stirred and aged for 30±2 minutes, and the aging temperature is maintained at 100°C to 103°C to obtain a hydrolyzed titanium liquid; (5) After step (4) is completed, heating and stirring are turned on, and the hydrolyzed titanium liquid is heated to boiling again within 10 minutes to 15 minutes, and a slightly boiling state is maintained. After boiling again for 2 hours to 2.5 hours, dilution water is added, and the total titanium concentration of the hydrolysis system is maintained at 146 g / L to 153 g / L. After boiling again for 3±0.2 hours, the hydrolysis is terminated to obtain a hydrolyzed slurry; (6) The hydrolyzed slurry is filtered, washed, and then pressed through a diaphragm to obtain electronic grade titanic acid.

2. The hydrolysis method for preparing electronic grade metatitanic acid by sulfuric acid process according to claim 1, characterized in that: The total titanium concentration of the industrial titanium liquid is 155g / L to 170g / L based on the mass of TiO2, the F value is 1.84 to 1.90, the iron-titanium ratio is 0.60 to 0.80, and the trivalent titanium content is 1g / L to 3g / L.

3. The hydrolysis method for preparing electronic grade metatitanic acid by sulfuric acid process according to claim 2, characterized in that: The total titanium concentration of the industrial titanium liquid is 160g / L to 170g / L based on the mass of TiO2, the F value is 1.86 to 1.88, the iron-titanium ratio is 0.68 to 0.78, and the trivalent titanium content is 1.5g / L to 2.5g / L.

4. The hydrolysis method for preparing electronic grade metatitanic acid by sulfuric acid process according to claim 1, characterized in that: In step (2), the mass ratio of the total TiO2 mass in the industrial titanium liquid to the soda ash in the alkali solution is 0.13-0.17; the alkali solution is a sodium hydroxide aqueous solution with a mass concentration of 9%-11%.

5. The hydrolysis method for preparing electronic grade metatitanic acid by sulfuric acid process according to claim 1, characterized in that: The total titanium concentration of the seed solution is 130 g / L to 137 g / L in terms of TiO2 mass, the seed F value is 1.62 to 1.69, and the stability is 125 mL to 150 mL.

6. The hydrolysis method for preparing electronic grade metatitanic acid by sulfuric acid process according to claim 5, characterized in that: The total titanium concentration of the seed solution is 133 g / L to 135 g / L in terms of TiO2 mass, and the seed F value is 1.65 to 1.

67.

7. The hydrolysis method for preparing electronic grade metatitanic acid by sulfuric acid process according to claim 5, characterized in that: In step (3), the mass ratio of the seed solution added is 2.0% to 2.6%; preferably, the mass ratio of the seed solution added is 2.1% to 2.4%.

8. The hydrolysis method for preparing electronic grade metatitanic acid by sulfuric acid process according to claim 1, characterized in that: In step (6), the iron impurity content is maintained below 30 ppm after washing.

9. The hydrolysis method for preparing electronic grade metatitanic acid by sulfuric acid process according to claim 1, characterized in that: The washing in step (6) includes first washing, bleaching, rinsing and third washing.

10. The hydrolysis method for preparing electronic grade metatitanic acid by sulfuric acid process according to claim 1, characterized in that: The specific surface area of ​​the electronic grade metatitanic acid is greater than 350m 2 / g, TiO2 purity is greater than or equal to 99%.